The Impact of Carbon Pricing on Economic Attractiveness and Environmental Performance: A Structural Equation Modeling Approach Across Asia-Pacific - Andi Aulia Khairunnisa; Khusnul Hafifah Farwati; Addinisa Mellyfitria (Publication of the International Journal and Academic Research, 2025)
This study examines the multidimensional effects of carbon pricing on environmental quality and economic attractiveness in Asia-Pacific countries, applying Partial Least Squares Structural Equation Modeling (PLS-SEM). Economic attractiveness is proxied by foreign direct investment (FDI) indicators, while environmental quality is assessed through the Environmental Performance Index (EPI) and related metrics. The model incorporates four latent constructs: carbon pricing, environmental performance, fiscal capacity, and FDI. Results indicate that carbon pricing exerts a statistically significant and positive impact on both environmental quality and government revenue, reinforcing its role as a policy instrument with dual ecological and fiscal benefits. Notably, carbon pricing also demonstrates a direct positive influence on FDI, suggesting that credible and transparent environmental policies may enhance a country’s investment appeal. However, indirect effects via environmental performance and fiscal capacity are not statistically significant. By integrating environmental, fiscal, and investment dimensions, this study contributes a novel empirical framework to the literature on sustainable development policy in emerging economies. The findings offer actionable insights for policymakers aiming to design carbon pricing strategies that support both environmental goals and economic competitiveness.